Quad bike related injury in Victoria, Australia. Issue 6 (16th September 2013) - Clapperton, Angela J; Herde, Emily L; Lower, Tony
Abstract: Objective: To enumerate and describe fatal and hospital‐treated injury associated with quad bike use in Victoria. Design: Retrospective descriptive analysis of coronial records and hospital‐treated injury data (2002–03 to 2010–11). Main outcome measures: Number of quad bike‐related fatalities, hospital admissions, emergency department (ED) presentations, and results of a trend and severity analysis (International Classification of Disease‐based Injury Severity Score; ICISS). Results: There were 19 fatalities, 766 hospital admissions and 816 ED presentations. The peak age group for fatalities and admissions was 15–29 years (26.3% and 27.9%, respectively), with children 0–14 years being the most common group presenting to EDs (32.2%). Males were strongly overrepresented (84.2% of fatalities, 73.8% of admissions and 71.2% of ED presentations). Intracranial injury (26.3%), fractures (15.8%) and traumatic asphyxiation (15.8%) were the most common injuries among fatal cases. Fractures accounted for half all admissions. Twenty‐eight per cent of admissions were classified as "serious" (ICISS, ≤ 0.941) and, over the 9‐year study period, the frequency of admissions increased significantly by an estimated 41.4% (95% CI, 9.6%–78.9%). This was significant for males (53.2%; 95% CI, 11.5%–104.4%) and people aged 15–29 years (163.1%; 95% CI, 75.2%–253.7%). Conclusion: Quad bikes are imposing a significant injury burden in Victoria. Fatalities are frequent, while the number of admissions, often serious, increased over the study period. Children were involved across all levels of severity. A range of prevention approaches, such as mandatory fitting of crush protection devices to protect riders in the event of a roll over, are required.